Al-Qur’an dan Pendidikan Anak: Surat Luqman Ayat 12-19 - Moh. Solehuddin; Nur Wahib (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2020)
The changing times often make children behave impolitely and even rudely because of the influence of globalization, information and digital. So only faith can stem this negative impact. Therefore, Islamic education is very necessary in this case. And the author chooses Surah Luqman verses 12-19 because it is full of advice to build morals and increase faith in children. The results of the study show that: (1) how the Koran provides an overview of children's education (2) The concept of Children's Education in the perspective of the Koran Luqman verses 12-19 describes the emphasis on the material and methods of children's education. The educational materials taught include creed, sharia, and moral education. The method used is maw'idah (advice). (3) Actualization of the development of the concept of children's education in this globalization era is by developing Islamic religious curriculum based on life skills, Conducting a contextual approach to PAI learning in the aspect of faith, Implementing the integration of faith with science and technology.